Activity of Gemifloxacin against Penicillin- and Ciprofloxacin-Resistant Streptococcus pneumoniae Displaying Topoisomerase- and Efflux-Mediated Resistance Mechanisms - Heaton, Victoria J. (American Society for Microbiology, 1999)
Nine penicillin-resistant Streptococcus pneumoniae clinical isolates from Northern Ireland, resistant to ciprofloxacin (MICs, 2 to 64 μg/ml) through topoisomerase- and/or reserpine-sensitive efflux mechanisms, were highly susceptible to gemifloxacin (MICs, 0.03 to 0.12 μg/ml). Two strains (requiring a ciprofloxacin MIC of 64 μg/ml) carried known quinolone resistance mutations in parC, parE, and gyrB, resulting in S79F, D435V, and E474K changes, respectively. Thus, gemifloxacin is active against clinical strains exhibiting altered topoisomerase and efflux phenotypes.